Taming Childhood? A Critical Perspective on Policy, Practice and Parenting - Creasy, Rob.; Corby, Fiona; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book explores the links between recent reports of increasing levels of unhappiness and mental health problems amongst children and young people, and changes within childhood which restrict and reduce opportunities for children to develop and maintain resilience. Although in academic terms children may be viewed as beings, Creasy and Corby posit that there is much to suggest that for parents, practitioners and policy-makers, children are primarily seen as becomings. The book argues that viewing children as becomings, together with the idea that childhood is fraught with danger, contributes to practices and policies which can be seen as making childhood tame. This taming of childhood leads to an impoverished childhood that does not provide the space that children need to grow and develop. Furthermore, Taming Childhood? challenges the idea that young adults are 'snowflakes', unable to cope with everyday pressures. Students and scholars across a range of social science disciplines will find this book of interest. .
1. Introduction -- 2. The Context of Childhood -- 3. Tameness -- 4. Home and Family -- 5. Taming in the early years -- 6. Tameness at school -- 7. Taming childhood?.
Keywords: Sociology; Social groups; Family policy; Sociology of Family, Youth and Aging; Children, Youth and Family Policy